Структурно-логическая схема снижения массогабаритных параметров турбогенераторов - Шевченко, Валентина Владимировна; Масленников, Андрей Михайлович (Приазовский государственный технический университет, 2015)
Для поддержания конкурентоспособности отечественных турбогенераторов (ТГ) необходимо вести работы по снижению удельного массогабаритного параметра (кг/кВт) в двух направлениях: выполнение соответствующих инженерно-проектировочных и расчетно-конструкторских работ с учетом возможности обеспечения необходимыми технологическими процессами на предприятии-изготовителе и с учетом экономичности решений и целесообразности финансовых затрат. Получена структурно-логическая схема технических требований к проектированию современных ТГ, которая включает три аспекта: проектный, эксплуатационный и экономический.

In order to maintain the competitiveness of turbo-generators (TG) it is necessary to reduce their mass and dimensions, that is to work in two main directions: to fulfil engineering, calculation and design work; to consider the possibility to provide technological processes at the enterprise where TG are produced. It is necessary to take into account the efficiency of additional expenses on extra tooling, materials and wages. These indicators form the cost of the production unit and determine the competitiveness of the TG. The structural logic of technical requirements for the design of modern TG was obtained. The formulations of requirements are the priority analysis that must be applied when choosing weight and size parameters of TG. The structural logic scheme of the design was compiled and it includes three main aspects: design, maintenance and cost. These aspects are the basis of the design of TG. In each section, the main point can be distinguished: 1) The design branch contains a list of demands to optimize the design of TG and the ways to manufacture it; 2) The maintenance branch deals with human resources management, staff qualification, wages and working conditions; 3) The cost defines the choice of a design and the quality; Proper quality of the TG can be achieved only by providing reliable communication of all the components of structural and logic scheme.
The scheme to reduce turbo-generator mass and dimensions
Keywords: турбогенераторы; конкурентоспособность; удельные массогабаритные параметры; структурно-логическая схема; turbogenerator; competitiveness; specific weight and size parameters; structural logic scheme